Comparison of Mortality between Japanese Peritoneal Dialysis and Hemodialysis Patients: A 5-Year Multicenter Follow-Up Study. (30th May 2012) - Suzuki, Kazuko; Konta, Tsuneo; Ichikawa, Kazunobu; Ikeda, Ami; Niino, Hiroki; Hoshikawa, Masato; Takahashi, Toshiyuki; Abiko, Hiroshi; Ito, Minoru; Masakane, Ikuto; Matsunaga, Tomohito; Kudo, Kosuke; et al.
Abstract : To examine the relationship between dialysis modality and prognosis in Japanese patients, we conducted a prospective multicenter observational study. We recruited 83 background-matched peritoneal dialysis (PD) and 83 hemodialysis (HD) patients (average age, 64.9 years; men, 53.6%; diabetic patients, 22.9%; median duration of dialysis, 48 months in all patients) and followed them for 5 years. During the follow-up period, 27 PD patients (16 cardiovascular and 11 non-cardiovascular deaths) and 27 HD patients died (14 cardiovascular and 13 non-cardiovascular deaths). There were 8 PD patients switched to HD, and 6 PD patients received renal transplantation. Kaplan-Meier analysis revealed that the crude survival rate was not significantly different at the end of 5 years (PD 67.5% versus 67.5%, log-rank P = 0.719 ). The difference in cardiovascular and non-cardiovascular mortalities between PD and HD was not statistically significant. Multivariate Cox analysis showed that the independent predictors for death were age and serum albumin levels, but not the dialysis modality. This study showed that the overall mortality was not significantly different between PD and HD patients, which suggests that dialysis modality might not be an independent factor for survival in Japanese patients.